The Age-Modified Shock Index: Predicting Massive Transfusion and Mortality in Traumatic Injury Patients - Soo Bin Choi; Suck Ju Cho; Seok-Ran Yeom; Sung-Wook Park; Young Mo Cho; Up Huh; Yeaeun Kim; Dongman Ryu; Chanhee Song; Won Ung Tae; Il Jae Wang (Emergency Medicine International)
Conclusion: Indices other than AMSI that are easier to compute may be more useful for the prognostic evaluation of patients with traumatic injuries.